Amlodipine-Candesartan Combination: A Cost-Effective Strategy for Successful Therapy of Hypertension - Fitria, Najmiatul; Zazna Syaputri, Yolanda; Mardatillah, Mardatillah; Akram, Muhammad; Nasif, Hansen (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Introduction: The combination of amlodipine and candesartan can have a better effect, although the cost-effectiveness analysis was not yet determined. This research aimed to establish the Incremental Cost-Effectiveness Ratio (ICER) value among outpatients with hypertension who used amlodipine-candesartan. Method: This research is a descriptive study that retrospectively gathered data from medical records. It focused on information for hypertensive patients at Universitas Andalas Hospital in 2021. This study compared the standard treatment involving amlodipine-candesartan and sole amlodipine, next to calculate the ICER using cost-effectiveness analysis. Results: Out of the total population of 284, as many as 73 patients were involved in this study. Among these, 21 patients (28.77%) were treated with amlodipine alone, while 52 (71.23%) received an amlodipine-candesartan combination. The Incremental Cost-Effectiveness Ratio (ICER) for reducing systolic blood pressure was IDR 74,738.10 per one mmHg decrease in the northeast quadrant of the cost-effectiveness chart. The ICER for lowering diastolic blood pressure was IDR 205,918.24 per one mmHg decrease in the northeast quadrant on the cost-effectiveness chart. Conclusion: The cost of the amlodipine-candesartan combination yields superior effects; however, warranting a probabilistic sensitivity analysis to determine its ICER robustness is essential for its effective implementation